2001
DOI: 10.1258/0023677011911390
|View full text |Cite
|
Sign up to set email alerts
|

The cage preferences of laboratory rats

Abstract: Preference tests were used to assess a range of enrichment options for rats kept under standard New Zealand (and similar) caging conditions. The rats did not show significant preferences for most of the options, over an empty cage. The exceptions were shredded paper, a nesting box and a semi-enriched condition incorporating a range of modifications. These cage modifications are recommended for the enrichment of laboratory rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…As the dam could possibly avoid the enriched compartment, one could find evidence for adverse effects of environmental enrichment. It has been suggested that rats prefer, when given a choice, nesting material and nesting boxes, but less so other enrichment objects, over living in a standard cage (Patterson-Kane et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As the dam could possibly avoid the enriched compartment, one could find evidence for adverse effects of environmental enrichment. It has been suggested that rats prefer, when given a choice, nesting material and nesting boxes, but less so other enrichment objects, over living in a standard cage (Patterson-Kane et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Nesting is widely acknowledged to be an important behaviour for female and male rats (Patterson-Kane et al 2001). Twelve inbred Hooded Norway rats (6 males, 6 females) housed in standard cages in groups of four preferred a cage with nesting material to a cage without (Patterson-Kane et al 2001).…”
Section: B Environmental Complexitymentioning
confidence: 99%
“…Twelve inbred Hooded Norway rats (6 males, 6 females) housed in standard cages in groups of four preferred a cage with nesting material to a cage without (Patterson-Kane et al 2001). Five female Wistar rats housed in a group always showed a significant preference for a cage containing a nest-box regardless of nest-box design (Patterson-Kane 2002a).…”
Section: B Environmental Complexitymentioning
confidence: 99%
“…from white light and conspecifics: Townsend, 1997;Manser et al, 1998;Eskola et al, 1999), enhance the options for expressing thigmotactic behaviour, and also increase willingness to utilize the open part of the cage (Anzaldo et al, 1994(Anzaldo et al, , 1995Lawlor, 2002;Abou-Ismail et al, 2010). Consistent with this, laboratory rats show a strong preference for objects that provide enclosed spaces within the cage such as retreats, nest boxes and polypropylene standard mouse (M2 type) cages (Bradshaw and Poling, 1991;Chmiel and Noonan, 1996;Townsend, 1997;Manser et al, 1998;Patterson-Kane et al, 2001). The types of enrichment item and the way in which they are provided should thus be carefully considered when designing an environmental enrichment protocol for captive animals such as laboratory rodents.…”
Section: Discussionmentioning
confidence: 92%